The Traditional Uses, Phytochemistry, Pharmacokinetics, Pharmacology, Toxicity, and Applications of Corydalis saxicola Bunting: A Review - Guo, Yanru; Zhao, Linjun; Chang, Botao; Yu, Jia; Bao, Jiangping; Yao, Qi; Luo, Jun (Frontiers in Pharmacology, 2022)
Background: Corydalis Saxicola Bunting(CSB) belongs to genus Corydalis (Papaveraceae). Generally, it is called “Yan-huang-lian” in the Chinese folk. Traditionally, it is used to treat acute conjunctivitis, corneal pannus, acute abdominal pain, hemorrhoidal bleeding, haematochezia, swelling, hepatitis, cirrhosis and liver cancer based on traditional Chinese medicine(TCM) concepts. Purpose: This review intents to provide a comprehensive and critical analysis on the traditional uses, phytochemistry, pharmacokinetics, pharmacology, toxicity, and clinical applications of CSB and to assess its therapeutic potential. Methods: CSB related literatures were searched and screened from available databases. The selected literatures provided reliable source identification evidences. Results: In traditional medicine concepts, CSB has the effects of clearing away heat and detoxification, eliminating dampness, relieving pain, and stopping bleeding. Its modern pharmacology includes hepatoprotective, anticancer, analgesic, antibacterial, antioxidative, and other effects. Further, some pharmacological effects support its traditional uses. The CSB total alkaloids (CSBTA) are the main components isolated from this plant, and they exert the major of the pharmacological effects. Toxicological studies have shown that the toxicity of CSBTA is mild and reversible in rodents and beagle dogs. Currently, CSB is routinely used to cure hepatitis, hyperbilirubinemia, liver cancer, and colorectal cancer in combination with other drugs in clinic. Conclusion: Although the present study summarizes the botany, phytochemistry, pharmacokinetics, pharmacology, toxicity, and clinical applications of this plant, it is still necessary to systemically evaluate the chemistry, pharmacology, safety of the extracts or compounds from this plant before or in clinical trials in the future. Meanwhile, except for liver-related diseases, cancers, inflammatory-related diseases, and pains may be new research directions of this ethnomedicine.